Construction of a Scale for Emotions Management of the Educational Supervisors in the Sultanate of Oman - Salim K. Al Hosni; Ali A. Zamili; Hussain Al Kharusi; Ali M. Kazem (Sultan Qaboos University, 2014)
This study aimed to construct of a scale for emotions management of the educational supervisors in the Sultanate of Oman. It aimed to find out its psychometric properties in terms of validity, reliability, and performance norms. The sample size consisted of 335 supervisors from the Omani educational governorate. The scale was applied during the first semester of the academic year 2010-2011. The validity was verified by three methods: face validity, factorialvalidity and concurrentvalidity. Since there were no significant differences in the scale averages of males and females, the norms were derived for both males and females combined. Finally, a number of recommendations and suggestions have been introduced.